Biochar and environmental sustainability: Emerging trends and techno-economic perspectives. (July 2021) - Khan, Nawaz; Chowdhary, Pankaj; Gnansounou, Edgard; Chaturvedi, Preeti
Graphical abstract: Highlights: Biochar uses for sustainable environmental management are discussed. Organic and inorganic pollutants removal by biochar are critically appraised. Challenges in field of biochar development & applications are mentioned. Techno-economic aspects of biochar are discussed in detail. Abstract: Environmental pollutants including emerging contaminants are a growing concern worldwide. Organic wastes, such as food waste, compost, animal manure, crop residues, and sludge are generally used as feedstock. The conventional treatment methodologies (primary and secondary treatment process) do not mitigate or remove pollutants effectively. Hence, an effective, low-cost, and environmentally friendly tertiary treatment process is an urgent need. Biochar finds interesting applications in environmental processes like pollutant remediation, greenhouse gas mitigation, and wastewater treatment. Studies have shown that different types of adsorbents (biochars) like, native and engineered biochar are being used in the removal or mitigation of heavy metals, polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls, pesticides, disinfectants, polychlorinated dibenzofurans, and dibenzo- p -dioxins from contaminated sites for environmental management. The review discusses ample studies which can offer solutions for environmental sustenance and management and the emerging trends and techno-economic prospectives of biochar for sustainable environmental management.